2022
DOI: 10.1038/s41380-022-01734-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain alterations associated with suicidal thoughts and behaviors in young people: results from 21 international studies from the ENIGMA Suicidal Thoughts and Behaviours consortium

Abstract: Identifying brain alterations associated with suicidal thoughts and behaviors (STBs) in young people is critical to understanding their development and improving early intervention and prevention. The ENIGMA Suicidal Thoughts and Behaviours (ENIGMA-STB) consortium analyzed neuroimaging data harmonized across sites to examine brain morphology associated with STBs in youth. We performed analyses in three separate stages, in samples ranging from most to least homogeneous in terms of suicide assessment instrument … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, Richard-Devantoy et al used a Go-No-Go task and found that deficits in cognitive inhibition (in relation to the IFG, thalamus, OFC, and parietal cortex) were related to the depressive, but not specifically, STB vulnerability risk ( 27 ). In contrast, the meta-analysis involving neuroimaging studies using the monetary incentive delay task and the stop signal task with over 5,000 participants aged 9–11 could not delineate between those with suicidal ideation from those with suicidal behaviors ( 28 ). Although our belief is that there is a difference in this domain between those with suicidal ideation and those who attempt, evidence is scant and will depend on future work of our own and others.…”
Section: Resultsmentioning
confidence: 97%
“…However, Richard-Devantoy et al used a Go-No-Go task and found that deficits in cognitive inhibition (in relation to the IFG, thalamus, OFC, and parietal cortex) were related to the depressive, but not specifically, STB vulnerability risk ( 27 ). In contrast, the meta-analysis involving neuroimaging studies using the monetary incentive delay task and the stop signal task with over 5,000 participants aged 9–11 could not delineate between those with suicidal ideation from those with suicidal behaviors ( 28 ). Although our belief is that there is a difference in this domain between those with suicidal ideation and those who attempt, evidence is scant and will depend on future work of our own and others.…”
Section: Resultsmentioning
confidence: 97%
“…Our study is a comprehensive assessment of how well different suicide risk assessment instruments relate to each other and the extent to which they can be used interchangeably. Harmonization reduces heterogeneity and increases power for discovery analyses, but also enables the assessment of the generalizability of studies and opens up the opportunity to investigate other aspects such as interactions and individual variation analysis (van Harmelen et al, 2021). Identification of correlates of suicide risk may be improved by increasing sample sizes, and by pooling data across studies to detect small effect sizes, which may result from large variance in underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these consortia include the International Suicide Genetics Consortium (Mullins et al, 2022) and the Enhancing NeuroImaging Genetics through Meta-Analysis Suicidal Thoughts and Behaviour (ENIGMA-STB) consortium (van Velzen et al, 2022). The aim of ENIGMA-STB is to study the neural correlates of STB, by bringing together research groups around the world that have collected both neuroimaging data and assessed STB in individuals with and without mental disorders.…”
Section: Key Pointsmentioning
confidence: 99%
“…The two studies that met this definition showed a general agreement with the END model, highlighting frontotemporal structural and right OFC functional aberrations in youth with bipolar disorder and self-harm [ 60 , 61 ]. The largest study among the 8 additional studies was the ENIGMA Suicidal Thoughts and Behaviours (ENIGMA-STB) consortium study (comprised of multiple samples, including a sample of 577 young people with mood disorders and a transdiagnostic sample with 253 healthy controls, 432 clinical controls, and 91 young people with a history of a suicide attempt), which did not show any morphological findings in the heterogeneous cohort of young people with a history of suicide attempts but showed a correlation of suicide attempt history with a smaller surface area of the frontal pole in the mood disorder cohort [ 65 ]. Even though the absence of findings in the heterogeneous cohort makes this study not directly comparable with the END model, it is worth mentioning that the frontal pole is adjacent to the lateral OFC, which may point to compatibility with the model.…”
Section: Discussionmentioning
confidence: 99%